Antibiotic-laden Bone Cement in Primary and Revision Hip and Knee Arthroplasty. Issue 20 (15th October 2018) - Gandhi, Rajiv; Backstein, David; Zywiel, Michael G.
Abstract : Antibiotic-laden bone cement (ALBC) has a number of different uses in primary and revision total joint arthroplasty. However, considerable controversy remains regarding how and when it is best used. The prophylactic use of low-dose ALBC in primary cemented total hip arthroplasty is well supported by the literature, conferring both clinical and economic benefits. In contrast, conclusive evidence on the clinical efficacy or economic benefit of the routine use of ALBC in primary total knee arthroplasty remains elusive. Given the currently available evidence, we cannot determine definitively whether the routine use of ALBC in primary total knee arthroplasty is justified, although selective use in patients with a high risk of infection seems warranted. The routine use of ALBC in revision total joint arthroplasty is well accepted, with good supporting evidence in studies of both aseptic and first-stage revision procedures. Although limited clinical evidence exists on the use of ALBC at the time of definitive component reimplantation after septic revision, the rationale for its use is strong.